O clube de mães e dos agricultores familiares de pindoba e sua mobilização política - BEZERRA, Jaqueline Araújo (2022)
This dissertation work discusses dynamics that can lead to the political mobilization of a Club of Mothers and Family Farmers of the Pindoba community, located in the rural area of the municipality of Paço do Lumiar, metropolitan region of São Luís. Field research was carried out from 2019 to 2020. Data emerged through informal conversations and direct observation during field visits. One question was presented as fundamental to understand the particularity of this Clube de Mães' performance: to what extent the formulations contained in the emergence of the first Clubs, between the 1960s and 1970s, are related to the dynamics of action of the object in question. In this sense, the dissertation work makes notes on the emerging political context of the new social movements in Brazil, pointing to different collective identities: women, rural and/or urban workers. with involvement in government programs to encourage family farming for its associates. The objective is to describe and analyze the role played by the Club with regard to institutional dynamics, making a brief history of this association, understanding how it presents its mobilizations and political articulations, with emphasis on social policies and/or programs and projects for the community. The empirical reality observed allowed me to highlight the uniqueness of the Clube de Mães e dos Agricultores Familiares located in a rural area with strong potential for family farming. It was possible to identify that, over time, it proposes to promote objectives of working in articulation with the intersectoral axis of social assistance policy, according to the regiment of its own Statute. It is exposed how the analyzed Club operates more as a civil society organization that mobilizes and executes social programs and policies, rather than a form of association based on gender or religious principles.